4-Hexyloxybenzamide. - Kwong, Huey Chong; Ab. Rahman, Mohamad Zaki; Mohamed Tahir, Mohamed Ibrahim; Silong, Sidik (International Union of Crystallography, 2011)
In the title compound, C13H19NO2, the dihedral angle between the benzene ring and the plane throught the non-H atoms of the amide group is 29.3 (1)°. The benzene ring and the alkane carbon skeleton plane are twisted slightly with respect to each other [5.40 (5)°]. In the crystal, molecules are oriented with the amide groups head-to-head, forming N-H...O hydrogen-bonded dimers. The dimers are connected by further N-H...O hydrogen bonds into a ladder-like motif along the b axis.